Assessment of the piriformis muscle and piriformis syndrome via Web of Science database: A bibliometric analysis - Polat, Sema; Tunç, Mahmut; Aksay, Ufuk Can; Sönmez, Elif İpek; Özşahin, Esin; Göker, Pinar (Medicine (Baltimore), 2024)
Background: Piriformis syndrome, which is seen as the cause of 0.3% to 6% of low back pain, is a painful condition that occurs as a result of compression of the piriformis muscle on the sciatic nerve. Although there are many studies in the literature about piriformis syndrome, no bibliometric analysis has been found. This study aims to evaluate piriformis syndrome and conduct a bibliometric analysis of studies related to piriformis muscle and syndrome. Methods: This study was conducted on March 27, 2024, using data recorded in the Web of Science Core Collection Database. The search was made as "Topic = Piriformis OR Piriformis Syndrome." Accordingly, 1345 results were found, and as a result of the necessary inclusion and exclusion criteria, 961 documents remained. The data was transferred to the VOSviewer software for further analysis. Results: 961 documents based on piriformis muscle or piriformis syndrome were obtained. The country with the most publications was reported to be the USA with 31.42%. Other countries are ranked at around 5% or less. While 9 of the top 10 most cited institutions are based in the USA, clinics that make significant research contributions also attract attention among these institutions. Journals that publish articles containing piriformis syndrome are prominently surgery, physical therapy, anatomy, and general medicine journals. The most repeated keywords were reported as piriformis syndrome, diagnosis, pain, muscle, sciatic nerve, and hip. In contrast, the most repeated clinical terms were reported as approach, surgery, piriformis muscle, injection, sciatica, and compression. Conclusion: The findings obtained in this study are thought to be important for understanding to providing literature with new perspectives on this subject. They will also focus on the missing parts of the subject from this perspective. Also, this study would provide a novel perspective to the studies about piriformis syndrome and contribute to the researchers about the limits of the topic, and being aware of the active journals that publish papers on this issue would facilitate the work of the researchers.